Evaluation of molecular diversity of new castor lines (Ricinus communis L.) using random amplifi ed polymorphic DNA markers - Zdenka Galova, Timea Kutka Hlozakova, Martin Vivodik, Zelmíra Balazova, (Horticultural Biotechnology Research, 2015)
The aim of this work was to detect genetic variability among the set of 32 castor genotypes using five random amplified polymorphic DNA (RAPD) markers. Amplification of genomic DNA of 32 genotypes, using RAPD analysis, yielded 41 fragments, with an average of 8.20 polymorphic fragments per primer. Number of amplified fragments ranged from 5 to 11, with the size of amplicons varied from 100 to 1200 bp. The polymorphic information content value ranged from 0.598 (RLZ 9) to 0.811 (RLZ 6) with an average of 0.746 and diversity index value ranged from 0.557 (RLZ 9) to 0.889 (RLZ 7) with an average of 0.784. The dendrogram based on hierarchical cluster analysis using unweighted pair group method with arithmetic average algorithm was prepared.